Fire on the mountain - Abbey, Edward 1927-1989 (HarperPerennial Modern Classics, 2012)
"Edward Abbey was a hero to environmentalists and rebels of every stripe. With Fire on the Mountain, this literary giant of the New West gave readers a powerful, moving, and enduring tale that gloriously celebrates the undying spirit of American individualism. This fiftieth anniversary edition, with an introduction by historian Douglas Brinkley, reminds readers of Abbey's powerful conviction that "a patriot must always be ready to defend his country against his government." John Vogelin's land is his life - a barren stretch of New Mexican wilderness mercifully bypassed by civilization. Then the government moves in. And suddenly the elderly, mule-stubborn rancher is confronting the combined land-grabbing greed of the county sheriff, the Department of the Interior, the Atomic Energy Commission, and the U.S. Air Force. But a tough old man is like a mountain lion: if you back him into a corner, he'll come out fighting"--P. [4] of cover
Reprint with new introduction. Originally published: New York : Dial Press, New York, 1962
Keywords: Grandfathers / New Mexico / Fiction; Eminent domain / United States / Fiction; White Sands Missile Range (N.M.) / Fiction; New Mexico / Fiction; USA